2023
DOI: 10.1177/10963480231191192
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Contactless Technologies Research in Hospitality and Tourism During the COVID-Pandemic

Abstract: Since the onset of the COVID-19 pandemic, the implementation of contactless technologies in hospitality and tourism has grown exponentially, making understanding consumer adoption of these technologies an important research area. A systematic literature review of relevant studies published in hospitality and tourism journals was conducted to identify three main subsets of the antecedents of contactless technologies adoption: system, user, and the environment. An analysis of 44 peer-reviewed articles from top h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Theory of Planned Behavior elucidates the link between attitudes, subjective norms, perceived behavioural control, and intentions for specific behaviours [11]. In the realm of contactless travel, this theory can be applied to investigate how attitudes towards contactless travel, perceptions of others' opinions, and beliefs in one's ability to use relevant technologies shape intentions to adopt contactless practices [12]. Research expanding on the theory has identified variations in demographic characteristics, moderation effects with such attributes playing a moderating role in attitudes and intentions [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theory of Planned Behavior elucidates the link between attitudes, subjective norms, perceived behavioural control, and intentions for specific behaviours [11]. In the realm of contactless travel, this theory can be applied to investigate how attitudes towards contactless travel, perceptions of others' opinions, and beliefs in one's ability to use relevant technologies shape intentions to adopt contactless practices [12]. Research expanding on the theory has identified variations in demographic characteristics, moderation effects with such attributes playing a moderating role in attitudes and intentions [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, tourism in cities undergoes a constant evolution, driven by a spectrum of novel technologies, products and business practices and models, which may emanate from within the tourism industry itself or result from the diffusion of innovations originating in other sectors. For example, emerging technologies such as virtual and augmented reality have gradually been applied in city exploration to elevate the tourist experience (tom Dieck & Jung, 2018); contactless technologies such as robot services and mobile payments have been used in tourism and hospitality industries to reduce health risks during the COVID-19 pandemic (Rathjens et al, 2023). The interplay between smart cities and smart tourism also creates a mutually reinforcing relationship where advancements in one sector benefit the other.…”
Section: Introductionmentioning
confidence: 99%